Interação de fibroblastos associados ao câncer em co-cultura com linguagens tumorias mamárias e a resposta terapêutica em o uso da melatonina - Maschio, Larissa Bazela [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Mammary tumors are the most common tumors among women and female dogs. Fibroblasts associated with cancer (CAFS) are the most abundant cells in the tumor microenvironment, able to mediate inflammatory responses acting in the differentiation and tumor progression. Melatonin is associated with mechanisms of action with oncostatics effects and oncoprotectors, and works to reduce the formation of surrounding fibroblasts in breast cancer. The objectives of this study were to assess the action of melatonin on mammary tumor cell lines human and canine metastatic (MDA-MB-231 and CF-41) and in co-culture with primary CAFS on cell viability and expression of proteins involved in the processes of angiogenesis, inflammation and apoptosis searching for the understanding of proteins interaction in the main signaling pathways active in the tumorigenic process. Cell viability was assessed by MTT assay and the semi-quantitative protein analysis by Membrane Antibody Array after treatment with melatonin. It was found that 1 mM of Melatonin reduced cell viability in both cell lines, human and canine CAFS and their co-culture (p <0.05). The semi-quantitative protein analysis after melatonin treatment showed a reduction of the expression of seven pro-angiogenic proteins and increased TIMP-1 and IL-6 protein in MDA-MB-231 cells and reduced IL-6 and MCP-1 and increased leptin, TGF-β, VEGF and thrombopoietin in the co-culture (p <0.05). Nineteen pro-inflammatory cytokine protein were reduced and I-309 increased in MDA-MB-231 cells (p <0.05). In the co-culture, six pro-inflammatory proteins were underexpressed and the IL-4, MCP-3 and SCF proteins were increased the expression (p <0.05). Twelve pro-apoptotic proteins increased and decreased expression of caspase-3 in MDA-MB-231 cells (p <0.05). In the co-culture, an increase of BIM, HPS27 and IGF-1R proteins and TNF-RII reduction was observed (p <0.05)...

As neoplasias mamárias são os tumores mais comuns nas mulheres e fêmeas caninas. Fibroblastos associados ao câncer (CAFs) são células abundantes no microambiente tumoral, capazes de intermediar respostas inflamatórias atuando na diferenciação e progressão tumoral. A melatonina está associada a mecanismos de ação com efeitos oncostáticos e oncoprotetores, e atua na redução da formação de fibroblastos circundantes no câncer de mama. Os objetivos desse estudo foram verificar a ação da melatonina nas linhagens tumorais mamárias metastáticas humana e canina (MDA-MB-231 e CF-41) bem como em co-cultivo com CAFs primários na viabilidade celular e na expressão de proteínas envolvidas nos processos de angiogênese, inflamação e apoptose, buscando o entendimento da interação destas proteínas nas principais vias de sinalização atuantes no processo tumorigênico. A viabilidade celular foi verificada pelo ensaio MTT e a expressão proteica pelo Membrane Antibody Array após o tratamento com melatonina. Verificou-se que 1 mM de melatonina reduziu a viabilidade celular em ambas as linhagens, CAFs humanos e caninos e em seus co-cultivos (p < 0,05). A análise proteica semiquantitativa, após tratamento com melatonina, mostrou redução da expressão de sete proteínas pró-angiogênicas e aumento das proteínas TIMP-1 e IL-6 nas células MDA-MB-231 e redução de IL-6 e MCP-1 e aumento da leptina, TGF-β, trombopoietina e VEGF na co-cultura (p < 0,05). Houve redução de dezenove proteínas pró-inflamatórias e aumento da citocina I-309 nas células MDA-MB-231 (p < 0,05). No co-cultivo, seis proteínas pró-inflamatórias apresentaram-se menos expressas e as proteínas IL-4, MCP-3 e SCF aumentaram sua expressão (p < 0,05). Das proteínas pró-apoptóticas, doze aumentaram a expressão e houve redução da caspase-3 nas células MDA-MB-231 (p < 0,05). Na co-cultura, houve aumento das proteínas BIM, HPS27 e IGF-1R e redução de...
Keywords: Genética; Cancer - Aspectos geneticos; Mamas - Cancer; Fibroblastos; Neovascularização; Melatonina